Masonry and partition wall layout part 1 (RFA-406_Rev B) - WOHA Designs PTE LTD; BUCG-ABC Joint Venture (BUCG-ABC JV); Web Structures (2023)
This record contains architectural contractor shop drawings of Brac University New Campus Project. It consists of both PDF and DWG version of drawings.